Studies on the basic issues relevant to sperm cryopreservation in humans - Huanhuan Hu; Xiaowei Shi; Guojie Ji; Rui Liu; Jing Zhang; Han Zhang; Mingwen Li (SAGE Publishing, 2020)
Rapid freezing and vitrification are becoming popular for sperm freezing in humans; however, basic and critical issues relevant to sperm cryopreservation remain to be resolved. The aims of the present study were to study the effects of osmolality of freezing medium, sperm concentrations, thawing methods, and sugars (sucrose and trehalose) on sperm motility and DNA integrity by rapid freezing using 0.5 ml standard straws loaded with 100 µl sperm each. The results showed that (1) the post-thaw recovery rates of total motility and progressive motility of sperm cryopreserved in freezing medium containing 0.25 M sucrose with 442 mOsm/kg osmolality were significantly higher ( p  < 0.05) than that of sperm cryopreserved in freezing medium containing 0.25 M sucrose with 536 mOsm/kg osmolality (36.5 ± 2.8% and 36.9 ± 1.7% versus 30.4 ± 1.9% and 30.3 ± 2.9%, respectively), (2) cryopreservation of both total and progressive motilities was not significantly affected ( p  > 0.05) by sperm concentrations in the range from 5 to 20 × 10 6  sperm/ml, (3) thawing method 37°C for 2 min was better than 42°C for 15 s in terms of post-thaw recovery rates of both total and progressive motilities ( p  < 0.05), (4) 0.25 M trehalose was better than 0.25 M sucrose in cryopreserving both total and progressive motilities ( p  < 0.05), and (5) sperm nuclear DNA is relatively resistant to the changes of the above factors compared with sperm motility. It was concluded that human sperm can be best cryopreserved by rapid freezing using 0.25 M sucrose or trehalose with osmolality 442 to 457 mOsm/kg at high sperm concentration followed by thawing at 37°C. Trehalose is a stronger cryoprotectant than sucrose for sperm cryopreservation.